2008
DOI: 10.2967/jnumed.107.044453
|View full text |Cite
|
Sign up to set email alerts
|

1-11C-Acetate Kinetics of Prostate Cancer

Abstract: 18 F-FDG is in widespread use in cancer imaging but has limited utility in staging and monitoring of prostate cancer. 1-11 CLabeled acetate, a substrate for the citric acid cycle, is superior. The kinetics of prostate tumors were investigated. Methods: Ten patients with primary prostate cancer, 10 with recurrent tumor, and 2 men with benign prostate hypertrophy were studied. After administration of 5.5 MBq/kg 1-11 C-acetate, dynamic PET of the pelvis was acquired for 20 min. Images were reconstructed with iter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 25 publications
5
43
1
Order By: Relevance
“…after AC injection showing an optimized power to differentiate benign hyperactivity in early imaging from recurrent cancer. Schiepers et al reported that the acetate kinetics of prostate cancer can be adequately described by a 3-compartement model and that early and late SUV are significantly different in primary and recurrent prostate cancer [28]. In the present study we have been able to show that limiting the study to the first PET frame 5 min.…”
Section: Discussionsupporting
confidence: 65%
“…after AC injection showing an optimized power to differentiate benign hyperactivity in early imaging from recurrent cancer. Schiepers et al reported that the acetate kinetics of prostate cancer can be adequately described by a 3-compartement model and that early and late SUV are significantly different in primary and recurrent prostate cancer [28]. In the present study we have been able to show that limiting the study to the first PET frame 5 min.…”
Section: Discussionsupporting
confidence: 65%
“…Schiepers et al used an IDIF method based on factor analysis to study patients with brain tumors using [ 18 F]-fluorothymidine (Schiepers et al, 2007b) and [ 18 F]-FDOPA (Fueger et al, 2010;Schiepers et al, 2007a). Although this method was never validated for brain studies against a reference input function, especially vis-à-vis the recovery coefficient used for partial volume correction, Schiepers et al had previously shown that it yielded reliable input functions for bone disorders with [ 18 F]-fluoride (Schiepers et al, 1997), in breast cancer with [ 18 F]-FDG (Schiepers et al, 1998), in prostate cancer with [ 11 C]-acetate (Schiepers et al, 2000(Schiepers et al, , 2002b(Schiepers et al, , 2008 (Schiepers et al, 2002a;Wu et al, 1995).…”
Section: How Often Is Image-derived Input Function Used In Positron Ementioning
confidence: 99%
“…After intravenous injection, 11 C-acetate is thus rapidly taken up by the myocardium, but the activity concentration in the myocardium decreases within minutes as radioactivity is released in the form of 11 C-O 2 . In contrast, 11 C-acetate has been shown to steadily accumulate in prostate cancer and other malignant tumors (114,123,127), indicating that the metabolic fate of acetate in cancer cells is fundamentally different. In cancer cells, an anabolic pathway seems to dominate, which uses acetate for synthesis of fatty acids and lipids.…”
Section: Tumor Lipid Metabolismmentioning
confidence: 99%